2018
DOI: 10.1038/s41592-018-0104-1
|View full text |Cite
|
Sign up to set email alerts
|

Reduced MEK inhibition preserves genomic stability in naive human embryonic stem cells

Abstract: Human embryonic stem cells (hESCs) can be captured in a primed state in which they resemble the postimplantation epiblast, or in a naive state where they resemble the preimplantation epiblast. Naive-cell-specific culture conditions allow the study of preimplantation development ex vivo but reportedly lead to chromosomal abnormalities, which compromises their utility in research and potential therapeutic applications. Although MEK inhibition is essential for the naive state, here we show that reduced MEK inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
76
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(77 citation statements)
references
References 39 publications
1
76
0
Order By: Relevance
“…EPI, epiblast; PE, primitive endoderm; TE, trophectoderm. (C) RNA-seq and protein expression data for DDX6 in primed and naive hESCs (Di Stefano et al, 2018). For RNA-seq data, n = 5, mean ± SD, unpaired Student's t test, ***p < 0.001.…”
Section: Ddx6 Controls Adult Stem/progenitor Cell Potency In a Contexmentioning
confidence: 99%
“…EPI, epiblast; PE, primitive endoderm; TE, trophectoderm. (C) RNA-seq and protein expression data for DDX6 in primed and naive hESCs (Di Stefano et al, 2018). For RNA-seq data, n = 5, mean ± SD, unpaired Student's t test, ***p < 0.001.…”
Section: Ddx6 Controls Adult Stem/progenitor Cell Potency In a Contexmentioning
confidence: 99%
“…Given that the XX karyotype is stable following XCI, the unstable karyotype is likely due to the double dosage of X-linked genes. While we were preparing this manuscript, it was reported that a lower concentration of Mek inhibitor was able to partially stabilise the XX karyotype (Di Stefano et al, 2018). We have tested this and find that low MEK inhibitor further stabilises Xmas ESC karyotype when using our improved conditions (data not shown), but still does not solve the problem entirely.…”
Section: Discussionmentioning
confidence: 88%
“…Further widespread loss of DNA methylation, including at repetitive elements and imprinting control centres is observed when female ESCs are cultured in conditions that promote ground-state pluripotency, despite male ESCs tolerating such conditions (Choi et al, 2017a;Choi et al, 2017b;Habibi et al, 2013;Ooi et al, 2010;Schulz et al, 2014;Yagi et al, 2017). Female ESCs are also karyotypically unstable, with XO cells rapidly dominating cultures (Choi et al, 2017b;Yagi et al, 2017;Zvetkova et al, 2005), which is also observed in human female embryonic stem cells (Di Stefano et al, 2018). These complications additionally arise when somatic female cells are reprogrammed to induced pluripotent stem cells (iPSCs) (Milagre et al, 2017;Pasque et al, 2018;Song et al, 2019), suggesting that these are features of female pluripotency in culture that confound both research requiring such cells and future medical applications.…”
Section: Introductionmentioning
confidence: 99%
“…While different in vitro environmental conditions such as the use of naïve versus primed culture medias or single-cell isolation can influence the propensity of cells to undergo genetic or epigenetic changes, all hPSC lines undergo continual cell division and thus may acquire alterations that influence their behavior. Specifically with regard to culture conditions, previous studies have shown that naïve culture conditions can contribute to chromosomal abnormalities in hPSCs [35] and thus require particularly close attention when being considered for disease modeling. Overall, genetic changes may come in the form of trisomies, copy number variations (CNVs), or single nucleotide variations (SNVs), with those conferring a selective growth advantage able to rapidly permeate through culture dishes.…”
Section: Unwanted Variancementioning
confidence: 99%